2018
DOI: 10.1111/apha.13163
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal macrophages and their interaction with the enteric nervous system in health and inflammatory bowel disease

Abstract: Over the past decades, there has been an increasing understanding of cellular and molecular mechanisms that mediate modulation of the immune system by the autonomic nervous system. The discovery that vagal nerve stimulation (VNS) attenuates endotoxin-induced experimental sepsis paved the way for further studies investigating neuro-immune interaction. In particular, great attention is now given to intestinal macrophages: several studies report the existence of both intrinsic and extrinsic neural mechanisms by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 79 publications
1
51
0
Order By: Relevance
“…The Mf4 population is primarily located deep in the mucosa and in the densely innervated submucosa and muscularis propria/externa (75) (Figures 2, 6). Thus, the Mf4 population might be specialized in nervous system interactions, as described in mice (195,(230)(231)(232)(233). However, further investigation is needed to better understand the origin and function of these cells in the human intestine.…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%
“…The Mf4 population is primarily located deep in the mucosa and in the densely innervated submucosa and muscularis propria/externa (75) (Figures 2, 6). Thus, the Mf4 population might be specialized in nervous system interactions, as described in mice (195,(230)(231)(232)(233). However, further investigation is needed to better understand the origin and function of these cells in the human intestine.…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%
“…Alpha7 nicotinic acetylcholine receptor (α7nAChR), firstly identified in the autonomous nervous system, is a ligand-gated ion channel exerted as a regulator in cognitive processes through the modulation of specific neurotransmitters (Marrero et al, 2011; Liu and Su, 2012; Lu et al, 2014). More recently, resident macrophages in different tissues proved to highly express α7nAChR, and the activation of this receptor inhibits the production of inflammatory cytokines, thereby attenuating the local inflammatory response (Yu et al, 2013; Foucault-Fruchard et al, 2018; Meroni et al, 2018). Previous studies demonstrated that the α7nAChR activation mediated bowel, neural, and cardiovascular protection (Yu et al, 2013; Foucault-Fruchard et al, 2018; Meroni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, resident macrophages in different tissues proved to highly express α7nAChR, and the activation of this receptor inhibits the production of inflammatory cytokines, thereby attenuating the local inflammatory response (Yu et al, 2013; Foucault-Fruchard et al, 2018; Meroni et al, 2018). Previous studies demonstrated that the α7nAChR activation mediated bowel, neural, and cardiovascular protection (Yu et al, 2013; Foucault-Fruchard et al, 2018; Meroni et al, 2018). Consistent with these data, the administration of α7nAChR agonist has been shown to effectively prevent acute lung injury via inflammation suppression (Ge et al, 2017; Pinheiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In inflammatory bowel disease, the dynamics of blood monocyte differentiation into resident intestinal macrophages is likely altered 154 . Animal models of colitis show increased infiltration of monocytes and immature macrophages into the gut mucosa, which during inflammation subsequently differentiate into mature, proinflammatory macrophages and where they produce a large amount of proinflammatory mediators, such as tumour necrosis factor, interleukin‐6 and nitric oxide 155 . A study on myeloid cell populations isolated from either human colonic inflammatory bowel disease biopsy specimens or murine DSS‐ induced colitis tissue samples has identified that the macrophage‐monocyte balance within the colon is also altered during colitis, with pro‐inflammatory blood monocytes increasingly recruited to the lamina propria 156 .…”
Section: Introductionmentioning
confidence: 99%